OP24 Development and evaluation of a novel intervention providing insight into the tobacco industry to prevent the uptake of smoking in school-aged children. (2nd September 2014) - Szatkowski, L; Taylor, J; Taylor, A; Lewis, S; McNeill, A; Britton, J; Jones, L; Bauld, L; Parrott, S; Wu, Q; Bains, M
Abstract : Background: Cigarette smoking is the biggest preventable cause of morbidity and mortality in the UK, and large numbers of smokers become addicted whilst still at school. Recent evidence suggests that school-based interventions focusing on the ethics and exploitative tactics of the tobacco industry may be more effective in preventing smoking uptake in school-age children than conventional messages about health risks. We report an evaluation of students' and teachers' views of the acceptability, potential effectiveness and ways in which the first UK intervention of this kind, Operation Smoke Storm, could be strengthened. Operation Smoke Storm comprises three hour-long classroom sessions designed for use with secondary school students, in which they act as secret agents to uncover tobacco industry tactics through videos, quizzes, discussions and presentations. Methods: Eight focus groups were conducted with Year 7 (age 11–12) students (n = 80) who had participated in Operation Smoke Storm at two schools serving different socio-economic catchment areas in the East Midlands region. Eighteen face-to-face (n = 16) or telephone interviews (n = 2) were conducted with teachers who delivered the intervention. The focus groups and interviews were digitally audio-recorded, transcribed clean verbatim and analysed using the Framework method. Results: Generally, students enjoyed the 'secret agent' scenario of Operation Smoke Storm, and reported that they had acquired new knowledge about smoking and the tobacco industry, which appeared to strengthen their aversion to smoking. The majority of teachers felt confident about delivering the 'off the shelf' resource, although they would have welcomed more background information about the topic area and detailed guidance on steering student discussions. Teachers highlighted a need for the resource to be flexible and able to be implemented regardless of lesson length and teacher confidence and expertise. Students and teachers endorsed the idea of developing a 'booster' intervention to be delivered in Year 8, to recap and maintain the effects of Operation Smoke Storm, though again stressed the importance of practical considerations such as limited access to computing facilities. Participants also supported the development of printed information for students to take home to help initiate conversation and encourage parents to support their child to not experiment with tobacco. Conclusion: Students and teachers perceived Operation Smoke Storm to be an engaging resource which increased awareness about smoking related issues. The ideas and issues raised by students and teachers will be used to improve and extend Operation Smoke Storm for future use and further evaluation.